2009
DOI: 10.1007/s10552-009-9294-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed exposure to infections and childhood lymphomas: a case–control study

Abstract: The risk of lymphomas, especially NHL, might be higher when, due to lower exposure to several infectious agents, the relatively unmodulated immune system of a child is challenged by environmental stimuli that can trigger development of lymphomas. The results, however, need further confirmation, through more pertinent methodological designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
2
9
1
2
Order By: Relevance
“…31 In contrast, Rudant et al examined parental report of several immune-mediating factors in a population-based case-control study in France, and found an inverse association for repeated early common infections overall (OR=0.5, 95% CI: 0.3-0.9) and across each of the HL subtypes, although small numbers precluded statistical significance in the latter. 32 Finally, Michos et al did not find evidence for an association for seroprevalence for 9 common infectious pathogens at the time of HL diagnosis in 52 childhood cases and their matched controls, 33 however, their cross-sectional study design did not allow for proper temporality and a latency period between infection and lymphomagenesis.…”
Section: Discussionmentioning
confidence: 95%
“…31 In contrast, Rudant et al examined parental report of several immune-mediating factors in a population-based case-control study in France, and found an inverse association for repeated early common infections overall (OR=0.5, 95% CI: 0.3-0.9) and across each of the HL subtypes, although small numbers precluded statistical significance in the latter. 32 Finally, Michos et al did not find evidence for an association for seroprevalence for 9 common infectious pathogens at the time of HL diagnosis in 52 childhood cases and their matched controls, 33 however, their cross-sectional study design did not allow for proper temporality and a latency period between infection and lymphomagenesis.…”
Section: Discussionmentioning
confidence: 95%
“…The associations were more marked when breastfeeding lasted 6 months or more [OR = 0.7 (0.6–0.7) for HL and OR = 0.7 (0.3–1.4) for NHL]. In a study published since then, slightly less of the cases of HL and NHL than the controls were breastfed for 6 months or more 44…”
Section: Discussionmentioning
confidence: 99%
“…Age-related shifts in this balance between these two types of immune response are known [33,34], and polymorphisms of genes related to Th1/Th2 cytokines appear to be relevant in lymphoma etiology [35][36][37]. However, it is still unclear whether age-related imbalances in the type of immune response account for the increase in lymphoma risk associated with delayed infection [11].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with autoimmune disorders and other immune system disturbances are also known to be more susceptible to hematological malignancies [2,3], and infections from viral agents, such as the Epstein-Barr virus (EBV), the hepatitis C virus (HCV), and bacteria, such as Helicobacter pylori (HP), have been associated with an excess lymphoma risk [4][5][6][7][8]. Disruption of the immune response, following for instance monucleosis infection, has been proposed as a key factor in non-Hodgkin lymphoma (NHL) etiology, with adult infection showing a positive association, while childhood infection appears to convey protection [9][10][11].…”
Section: Introductionmentioning
confidence: 99%